XIZMATLAR SOHASI RIVOJLANISHINI TAʼMINLASHNING TASHKILIYI IQTISODIY MEXANIZMLARI SAMARADORLIGINI OSHIRISHDA ILGʻOR XORIJIY TAJRIBADAN FOYDALANISH (Marketing Journal, 2026)
This study examined advanced foreign experience in improving organizational and economic mechanisms for service sector development. Innovation support practices implemented in Japan, Germany, France, and CIS countries were analyzed. The impact of innovation infrastructure, technology transfer, commercialization of research outcomes, and private sector participation on development effectiveness was evaluated. Based on the findings, practical recommendations were developed to strengthen innovation activities, improve institutional mechanisms, and enhancecompetitiveness in the service sector. The results highlighted the importance of integrating international best practices into national development strategies.
Keywords: service sector, innovative development, organizational and economic mechanism, technology transfer, innovation commercialization, competitiveness, foreign experience.